Exposure to hot and cold environmental conditions does not affect the decision making ability of soccer referees following an intermittent sprint protocol - Taylor, Lee; Fitch, Natalie; Castle, Paul; Watkins, Samuel; Aldous, Jeffrey; Sculthorpe, Nicholas; Midgely, Adrian; Brewer, John; Mauger, Alexis (Frontiers in Physiology, 2014)
Soccer referees enforce the laws of the game and the decisions they make can directly affect match results. Fixtures within European competitions take place in climatic conditions that are often challenging (e.g. Moscow ~ -5oC, Madrid ~30oC). Effects of these temperatures on player performance are well documented; however, little is known how this environmental stress may impair cognitive performance of soccer referees and if so, whether exercise exasperates this. The present study aims to investigate the effect of cold (COLD; 5oC, 40% relative humidity (RH)), hot (HOT; 30oC, 40% RH) and temperate (CONT; 18oC, 40% RH) conditions on decision making during soccer specific exercise. On separate occasions within each condition, thirteen physically active males; either semi-professional referees or semi-professional soccer players completed three 90 min intermittent treadmill protocols that simulated match play, interspersed with 4 computer delivered cognitive tests to measure vigilance and dual task capacity. Core and skin temperature, heart rate, rating of perceived exertion and thermal sensation were recorded throughout the protocol. There was no significant difference between conditions for decision making (p > 0.05) despite significant differences in measured physiological variables (skin temperature = HOT 34.5 ± 5.1°C; CONT 31.2 ± 0.1°C and COLD 26.7 ± 0.5°C; p < 0.05). It is hypothesised that the lack of difference observed in decision making ability between conditions was due to the exercise protocol used, as it may not have elicited an appropriate and valid soccer specific internal load to alter cognitive functioning.